Inobservancia del debido proceso por parte del juzgador violentando las garantías constitucionales del trabajador establecidas en el código laboral - Arévalo Martínez, Ketty Johanna (2016)
Our overall objective of the research is to demonstrate that violations of workers' rights in this case Mr José Ramón Gómez since the claim of the right to compensation started as the labor inspectorate could not do a good job with respect to collection of items corresponding to compensation for unfair dismissal. An important thing to note is that while the relevant documents were presented at the labor inspectorate to be appropriate to the summons and failing signing the contract record where payment of compensation is agreed by the employer and worker the same was not fulfilled for that reason had to get to the courts where they continue irregularities irrespetándose, trampling the right of the worker.